1997
DOI: 10.4141/a96-078
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-induced depression of methane production and digestibility in the artificial rumen system (RUSITEC)

Abstract: . 1997. Lipid-induced depression of methane production and digestibility in the artificial rumen system (RUSITEC). Can. J. Anim. Sci. 77: 269-278. An artificial rumen (RUSITEC) equipped with eight fermenters was used to examine the effects of canola oil (CA), cod liver oil (CD) and coconut oil (CO) on methane production, dietary digestibility and rumen microbial populations. The experiment, repeated three times, involved two diets (100% grass hay or a 90%:10% wheat:hay mixture) either untreated (controls) or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
107
1
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 24 publications
17
107
1
7
Order By: Relevance
“…Fats have also been shown to depress CH 4 production (Dong et al 1997a;Machmuller and Kreuzer 1999;Dohme et al 2000). It has been shown that the medium chain fatty acids (C 8 -C 16 ) cause the greatest reduction in CH 4 production (Dohme et al 2000).…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fats have also been shown to depress CH 4 production (Dong et al 1997a;Machmuller and Kreuzer 1999;Dohme et al 2000). It has been shown that the medium chain fatty acids (C 8 -C 16 ) cause the greatest reduction in CH 4 production (Dohme et al 2000).…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 99%
“…The major problem associated with excessive fat addition (more than 5-6% of the ration) is that it depresses fiber degradation in the rumen (Dong et al 1997a;Mathison et al 1998), and reduces acetate production and milk fat content (Jenkins et al 1996;Ashes et al 1997). Mathison (1997) observed that digestibility of fiber was reduced with the addition of canola oil, such that the metabolizable energy content of the diet was not different from that of the control barley-based diet.…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of lipids creates a physical barrier on the surface of fibrous particles and prevents the action of bacterial enzymes on sites of potentially digestible NDF. Lipids reduce NDF degradation in the rumen (Ferlay and Doreau, 1992), but the magnitude of depression varies with lipid chemistry and quantity, animal species, and experimental conditions (Dong et al, 1997). Therefore, the usual recommendation is that the total fat content of diet should not exceed 50 g/kg of the feed dry matter (DM) to avoid depressions on intake and NDF digestibility, which, in its turn, would reduce the benefit of a larger energy density in the diet by the addition of lipid (Palmquist and Jenkins, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Ruminant CH 4 production has in the past been measured using respiration calorimetry from which prediction equations relating CH 4 production to dietary components have been derived (Blaxter and Clapperton 1965;Moe and Tyrrell 1979;Holter and Young 1992). In-vitro techniques (Czerkawski and Breckenridge 1977;Dong et al 1997) and isotopic methods (Murray et al 1976;Frances et al 1993) have also been used. Conditions with the use of respiration chamber, in-vitro techniques, isotopic method and assumptions of prediction equations cannot be related to cattle under production situations, where environmental temperature, meal size and frequency, and selection of feed components can affect intake, rate of digestion and retention time in the rumen.…”
mentioning
confidence: 99%